PROSPECTS AND POSSIBLE RISKS OF THE APPLICATION OF SMART CONTRACTS IN SCIENCE AND EDUCATION - Akhmetova , О.С.; Issayev , С.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
Important advantages of the potential use of blockchain in the scientific and educational field are security, immutability, transparency. By providing a framework for decentralized forms of government and smart contracts, while significantly reducing the potential for fraudulent and corrupt practices, this technology can help safeguard public interests and state sovereignty. Today, attempts are being made to develop various technological solutions based on blockchain for various areas of social interaction. One example is the drafting of smart contracts aimed at solving a number of tasks in scientific and educational activities. The article discusses the possibilities and prospects of using blockchain technology and smart contracts in science and education. The topic causes controversy among specialists: some are convinced of the effectiveness of the proposed solutions, while others point to the negative consequences and obstacles to the introduction of new technology. The authors analyzed possible ways of introducing blockchain technology and smart contracts in the field of education and science, as well as the possible risks associated with their use.